Centenary of the Birth of Dr. Alberto Hurtado Abbey (1901 - August 29, 2001) - Guerra-García, Roger (2001)
The scientific work of Professor Alberto Hurtado begins in 1925, being a resident at Boston City Hospital, where he works alongside Francis Peabody, showing sincere devotion to clinical research, which determines the appreciation of his peers and teachers, who invite you to stay with them in the famous Harvard University. Completed his medical training, he returned to Peru and began researching local issues; his doctoral thesis at the University of San Marcos is on the basal metabolism of the Peruvian Indian, that extends past work studying the effect of hypoxic environment on it.